Waste Water Treatment in a Nutshell - Fawcett-Hirst, William (Cranfield University, 2018)
3MT presented at the 2018 Defence and Security Doctoral Symposium.Water is vital to life on Earth so there is a great incentive for all water users to use it responsibly. There are a plethora of materials that can be used to treat water such as sedimentation, flocculation and biological processes as well as the most favoured for industrial explosives applications, carbon. but most of that carbon comes from non-renewable sources such as bitumen and coal. In order to provide water security to in an efficient and affordable way, new methods or materials need to be devised to reduce the costs associated with water treatment and potentially ‘close the loop’ and re-use the waste products from this process in obtaining the next generation of materials.
Keywords: 'Adsorption'; 'Waste'; 'Carbon'; 'DSDS18 3MT'; 'DSDS18'; 'Water Treatment Processes'